(untitled) (Bangladesh Journal of Bioethics, 2018)
Dear Readers, Happy Summer Holidays for all of us up in the Northern Hemisphere. While we are basking in the warmth of sunny days our friends in Australia are buying winter clothes. How strange is this world! And stranger are the creations who are supposed to look after all other organic and inorganic objects in this planet and maybe beyond. The simple virtues of ethical and value based behavior is often forgotten when we are focus on getting the best for ourselves without thinking or respecting the rights of others. The case of ethics in publication is not any different. We have few papers this issue but they are of extreme value and relevance: